Research on Performance Evaluation of Sponge City PPP Projects in the Yangtze River Delta Region - Cao, Jingru (International Journal of Global Economics and Management, 2024)
In order to alleviate urban water ecological problems and promote sustainable urban development, many cities in my country are building sponge cities. At present, the country is vigorously promoting the application of the PPP model for project construction. The national government departments are actively preparing for the construction of sponge cities, promoting the construction of sponge cities in 30 pilot cities across the country, and encouraging sponge city construction projects using the PPP model, attracting a large amount of social capital to participate, and promoting The PPP model has been widely used in sponge city construction projects. This article takes the sponge city PPP project as the research object. In order to scientifically and rationally evaluate the construction performance of the sponge city PPP project, and on the basis of studying and summarizing the characteristics of the sponge city PPP project model and the development status of the performance evaluation system in my country, we conduct an analysis of the content of the performance evaluation. and research; establish and select a performance evaluation index system; conduct a comparative analysis of this model with other commonly used models, and build a PSIR-based PPP project performance evaluation model based on the design flaws of the existing performance evaluation system; and analyze and summarize the data. , clarifying its specific application and impact in practice; finally, a summary and outlook of the entire research are given.